(untitled) (Brazilian Journal of Pharmaceutical Sciences, 2011)
The purpose of this study was to mask the bitter taste imparted by dihydroartemisinin (DHA) by the use of different coating materials. Trial-1 and trial-2 were conducted to prepare the DHA granules. The granules produced from trial-1 were irregular in shape and smaller in size while the trial-2 granules were more regular and larger in size. The granules obtained from both trials were then coated with two different coating methods, namely A and B, depending upon coating material. The trial-2 granules showed better flow properties than trial-1 granules. In vitro dissolution studies in phosphate buffer at pH 6.8 revealed that granules of trial-2B released only 34% ± 3 DHA in two minutes compared with trial-1A (57% ± 2), trial-1B (48% ± 2) and trial-2A (53% ± 7). The pleasant taste perception (PTP) test also confirmed the taste masking efficacy of trial-2B (P < 0.05). Scanning electron microscopy (SEM) revealed the more regular and smooth surface of trial-2B granules. In addition, the differential thermal and thermogravimetric analysis (TG-DTA) confirmed no interaction between the materials and pure DHA. DHA has shown its characteristic peaks in the x-ray diffraction (XRD) patterns which were also prominent in all the granules. In conclusion, the granules obtained from trial-2B displayed considerable decrease in the bitter taste of DHA thereby fulfilling the purpose of this study.